Effect of Triple Acupuncture Therapy Combined with Rehabilitation Training on CGRP Content in Peripheral Blood, Motor Function and Activity of Daily Living of Spinal Cord Injury Patients - Yinjie CUI; Qian WANG; Yue JIANG; Anren ZHANG (康复学报, 2016)
Objective:To observe the effect of triple acupuncture therapy combined with rehabilitation training on calcitonin gene-related peptide (CGRP) content in peripheral blood of spinal cord injury (SCI) patients.Methods:50 SCI patients meeting study criteria were randomly assigned to treatment group (n=25) and control group (n=25). Both groups received rehabilitation training, the treatment group was added with triple acupuncture therapy, and the control group was added with regular meridians acupuncture therapy for one time per day and one month as a course. All patients received three courses of treatment.25 healthy subjects were enrolled as normal control group. Before treatment, after one month, two months, and three months of treatment, CGRP content in peripheral blood of the two groups was detected, and the American spinal injury association (ASIA) motor score, ASIA sensory score, modified Barthel index (MBI) score were measured.Results:The CGRP content in the two groups was lower significantly than that in the normal control group (P<0.05). After one month of treatment, the CGRP content in treatment group was higher significantly than that in the control group (P<0.05). After three months of treatment, the ASIA motion score and ASIA feel score were significantly increased in the treatment and control groups (P<0.05). After two months, three months of treatment, MBI scale in the two groups was significantly increased, but there was not significant difference between the two groups (P>0.05). The CGRP content was correlated with ASIA motor score, ASIA sensory score and MBI score (P<0.05).Conclusion:Triple acupuncture therapy combined with rehabilitation training has an important effect on CGRP content in peripheral blood, ASIA motor score, ASIA sensory score and MBI score of SCI patients in the early phase of treatment, which suggests an important role of early comprehensive treatment on function remodeling of SCI patients. The CGRP content in peripheral blood may be a potential protein for functional recovery of SCI patients in the early stage.